Microstructure and tensile properties of binder jet printed 17–4 precipitation hardened martensitic stainless steel - Radhakrishnan, Jayaraj (2023)
A detailed understanding of the connections between processing – porosity – microstructure – mechanical properties of additively manufactured (AM) alloys is essential before they can be utilized for structural applications. Towards this end, the microstructure and tensile properties of 17-4 PH martensitic (α′) stainless steel fabricated using binder jet printing (BJP) were investigated and compared with those of the conventionally manufactured (CM) alloy. Results show that optimizing the printing parameters to increase the relative density of the final part also affects the grain size as well as the morphology and fraction of the δ phase. Hot isostatic pressing (HIP), employed to reduce porosity, also refined the microstructure by dynamic recrystallization. Tempering of the martensitic microstructure through a post-fabrication H1150 over-aging heat treatment improves the strain hardening capability of the alloy and hence enhances its ductility substantially due to the formation of reversed γ phase. The tensile strength and ductility rise asymptotically with the decrease in porosity, until a critical fraction of ∼1.7% is reached. The variation in porosity and δ phase fractions does not influence the strain hardening behavior of the H900 peak aged alloy. In the over-aged condition, the deformation behavior is affected by a combination of porosity, transformation induced plasticity of the γ phase, and Cu partitioning across the α′- δ interface.